2022
DOI: 10.47432/2022.38.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NPK and Sulphur on Growth, Yield and Chlorophyll Contents of Cauliflower (Brassica Oleracea L).

Abstract: Cauliflower is cultivated all around the world for its high nutritional value. In Pakistan, there is dire need to optimize the nutritional supplementation of cauliflower. Therefore, a field experiment was carried out to see the impact of NPK and sulphur on growth, yield and chlorophyll contents of cauliflower. The experiment was laid out according to Randomized Complete Block Design having ten treatments replicated thrice. The experiment was consisted of five levels of NPK (13:17:17, 15:18:18, 16:18:18, 16:19:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
1
2
Order By: Relevance
“…As seen from Table 6, it was determined that the average oil ratio obtained from interactions of both factors ranged from 3.22 to 3.71 %. Contrary to the findings of the study, in some previous studies which evaluated the effects of humic acid on the oil ratio, it was reported that with the application of HA, the oil ratio was increased (Khazaie et al, 2011;Rajpar et al, 2011;Alireza, 2012;Esmaili et al, 2016;Noroozisharaf and Kaviani, 2018). The results of the study could be affected by environmental factors such as extreme heat in the summer of the Ranya district, in which most of the days reached above 40 °C.…”
Section: Oil Ratiocontrasting
confidence: 94%
See 1 more Smart Citation
“…As seen from Table 6, it was determined that the average oil ratio obtained from interactions of both factors ranged from 3.22 to 3.71 %. Contrary to the findings of the study, in some previous studies which evaluated the effects of humic acid on the oil ratio, it was reported that with the application of HA, the oil ratio was increased (Khazaie et al, 2011;Rajpar et al, 2011;Alireza, 2012;Esmaili et al, 2016;Noroozisharaf and Kaviani, 2018). The results of the study could be affected by environmental factors such as extreme heat in the summer of the Ranya district, in which most of the days reached above 40 °C.…”
Section: Oil Ratiocontrasting
confidence: 94%
“…When the mean values of the protein ratio were examined in Table 6, it was seen that the average values of the protein ratio obtained as a result of each HA dose application varied between 7.42 and 9.25 %. Contrary to the study, some previous studies' results reported by Rajpar et al, (2011), El-Saber et al, (2014, Esmaili et al, (2016), andOktem andOktem, (2020), the protein ratio should have been increased in accordance with the increase of the humic acid doses. It could be stated that the environmental effects such as extreme heat and drought affected the results of this study, due to the temperature during protein formation stages being very high in the Ranya district.…”
Section: Protein Ratiocontrasting
confidence: 79%
“…Higher results for the reproduction of cauliflower after NPK treatment (150 + 100 + 100 kg/acre) may be attributable to the increase in enzymatic metabolism in the plants followed on by NPK application, which is responsible for increasing curd size, curd weight, and yield [22]. These results were also verified with the results of Ali et al [23], Kisko et al [24] and Ashraf et al [14]. Phosphorus application in adequate quantity during the early stage of plant growth boosted the production of primordial of reproductive parts [25].…”
Section: Reproductive Parameterssupporting
confidence: 66%
“…Its key roles include absorption of light, maintaining cell turgor pressure, activities of enzymes and decreasing the absorption of Na + and Fe + [12,13]. Optimization of macronutrients such as nitrogen, phosphorus and potassium are necessary for higher quality production of cauliflower [14]. This study was designed to optimize the best suitable doses of macronutrients for higher quality yield of cauliflower.…”
Section: Introductionmentioning
confidence: 99%